Behind closed doors: Freelance nurses and the reality of unmet care needs in Italian home care setting. Insight from a phenomenological descriptive study - Dante, Angelo; Marcotullio, Alessia; Checchi, Adriana; Caponnetto, Valeria; Masotta, Vittorio; Paoli, Ilaria; Petrucci, Cristina; Lancia, Loreto (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The term ‘Missed Nursing Care’ (MNC) refers to any aspect of nursing care that is not delivered, partially delivered, or delayed. MNC has significant negative consequences, including adverse patient outcomes, safety risks, and decreased job satisfaction. While extensively studied in hospitals, MNC in community healthcare settings remains under-researched, especially in Italy. This study aims to explore the phenomenon of MNC in Italian home care settings by documenting and analyzing the lived experiences of freelance nurses, focusing on the characteristics, influencing factors, and consequences of MNC as perceived by these healthcare professionals.Study Design. This is a descriptive phenomenological study.Methods. Using snowball sampling, 12 Italian freelance nurses were recruited and interviewed from November 2022 to February 2023. Data collection was based on in-depth interviews, that have been transcribed and analyzed using Giorgi’s phenomenological framework. The study report adhered to the COREQ-32 checklist for qualitative research.Results. Thematic analysis revealed four main themes: dimensions of MNC, organizational challenges, consequences of MNC, and family-nurse collaboration. Freelance nurses frequently addressed unmet fundamental and complex nursing needs, highlighting significant clinical, psychological, and economic impacts on patients and families. Organizational issues, such as rigid public service schedules and inadequate staffing, were identified as primary contributors to MNC. Families played a crucial role in managing care and collaborating with freelance nurses to ensure continuity.Conclusions. This study provides novel insights into MNC in Italian home care settings, emphasizing the critical role of freelance nurses in filling care gaps. The findings suggest the need for systemic changes to improve flexibility, staffing, and integration of public and private nursing services. Further research, particularly quantitative studies, is essential to validate these findings and explore broader implications for patient care and health outcomes.